2019
DOI: 10.1136/bmjopen-2019-029478
|View full text |Cite
|
Sign up to set email alerts
|

Experience of and access to maternity care in the UK by immigrant women: a narrative synthesis systematic review

Abstract: One in four births in the UK is to foreign-born women. In 2016, the figure was 28.2%, the highest figure on record, with maternal and perinatal mortality also disproportionately higher for some immigrant women. Our objective was to examine issues of access and experience of maternity care by immigrant women based on a systematic review and narrative synthesis of empirical research.Review methodsA research librarian designed the search strategies (retrieving literature published from 1990 to end June 2017). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 55 publications
3
63
0
1
Order By: Relevance
“…Despite a 38% worldwide reduction in maternal mortality, it is apparent that inequalities continue (WHO et al, 2019). Recurrent factors attributing in part to poor outcomes for immigrant women in the United Kingdom (UK) include lack of awareness of the availability of maternity services, lack of understanding of the purpose of antenatal appointments and limited English language proficiency (Higginbottom et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a 38% worldwide reduction in maternal mortality, it is apparent that inequalities continue (WHO et al, 2019). Recurrent factors attributing in part to poor outcomes for immigrant women in the United Kingdom (UK) include lack of awareness of the availability of maternity services, lack of understanding of the purpose of antenatal appointments and limited English language proficiency (Higginbottom et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…informed decision-making is a sizeable human rights element of reproductive health, but women commonly describe communication failures with health workers during pregnancy and birth (Khosla et al, 2016). Available health service reports indicate nearly 300,000 adults of Indian, Pakistani, Bangladeshi and Chinese ethnicities in England and Wales have experienced communication barriers with health-care professionals (HCPs) (Gill et al, 2011) and this is similar for women with limited to no English proficiency attempting to access maternity services (Higginbottom et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However there remains a considerable disparity in outcome within the population, with Black, Asian and Minority Ethic [BAME] and in particular migrant women continuing to have higher rates of stillbirth compared to white women [2]. The reasons for these inequalities in stillbirth rates are not clear, but are likely to be multifaceted and include underlying structural racism, socioeconomic disadvantage and associated stress and coping mechanisms, access and acceptability of health care and accessibility to public health messages around reducing perinatal mortality [3,4] Previous research has identified that migrant women's experience of maternity care in the UK is generally poorer than that of women born in the UK [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It would have enhanced the PI&E in the study to have engaged additional younger women and more women from different cultural backgrounds, such as vulnerable and disadvantaged communities [ 94 ]. Inequalities in power relationships within and beyond healthcare [ 95 ] and poorer outcomes, particularly for Black women, but also for Asian and other ethnic communities and migrant women should be addressed [ 85 ]. Organisations and doula groups focusing specifically on the needs of women of colour [ 96 , 97 ] and advocating for women and families facing multiple social disadvantage [ 50 ] are increasingly accessible as social media open up instant communications and networking.…”
Section: Discussionmentioning
confidence: 99%